Correlation analysis of cognitive dysfunction and fluctuations in serum fibroblast growth factor 21 (FGF21) levels in the overweight group: Cognitive dysfunction and fluctuations in serum FGF21) - Lyu, Guotian; Lu, Xiaoli; Meng, Qichang; Liu, Yanyan; Liu, Shuyan; Liu, Jieyi; Dong, Peng (Journal of Medical Biochemistry, 2025)
Objective: To explore the changing characteristics of cognitive function in overweight/obese (OWO) adolescents and analyze its relationship with the level of serum fibroblast growth factor 21 (FGF21). Methods: A total of 175 adolescents were selected and divided into a normal body mass index (BMI) group (n=50), an overweight BMI group (n=50), and an obese BMI group (n=75). All participants underwent assessment of anthropometric indicators (height, weight, waist circumference, BMI Z score). Fasting venous blood was collected to measure the level of serum FGF21 (by enzyme-linked immunosorbent assay (ELISA)), as were metabolic parameters such as fasting plasma glucose (FPG), fasting insulin (FINS), glycated hemoglobin (HbA1c), and lipid profiles (TC, TG, LDL-C, HDL-C). Overall cognitive function was evaluated via the Chinese version of the Montreal Cognitive Assessment Foundation Scale (MoCA-B), executive function was evaluated via the Wisconsin Card Sorting Test (WCST) (with a focus on analyzing the number of persistent errors/PE and the number of completed classifications/CC), and working memory was evaluated via the number span test (DST). Independent sample t tests or Mann‒Whitney U tests were used to compare the differences between groups. Pearson or Spearman correlation analysis was used to explore the relationships between serum FGF21 levels and cognitive indicators and metabolic parameters. Multiple linear regression was used to analyze the independent association between serum FGF21 and cognitive function scores (after adjusting for potential confounding factors such as age, sex, BMI Z Score, and HOMA-IR). Results: Compared with those of the normal individuals, the systolic blood pressure, diastolic blood pressure, fasting blood glucose, glycated hemoglobin and triglyceride levels of the adolescents in the obese group were greater (all P<0.05). Under the consistent or inconsistent stimulation conditions of the Flanker task, there was no statistically significant difference in the ACC between any two groups of adolescents. Compared with those in the normal body type group and the overweight group, the reaction time of adolescents in the obese group was prolonged (all P<0.05). In the n-back task, there was no statistically significant difference in the ACC between any two groups of adolescents. However, the response time of adolescents in the obese group in the 1-back and 2-back tasks was longer than that in the normal body type group and the overweight group (all P<0.05). Compared with those in the normal body type group, the serum FGF21 levels of adolescents in the obese group were greater (P=0.000). The results of the partial correlation analysis revealed that the reaction time of adolescents in the Flanker and n-back tasks was correlated with their BMI, body fat mass, waist circumference, waist‒hip ratio, FGF21 level, etc. (all P<0.05). Multiple linear regression analysis further confirmed that BMI was associated with prolonged response time in cognitively related behavioral tasks in adolescents (all P<0.05), and the level of FGF21 was correlated with the ACC in the 2-back task (P=0.000) and the response time to inconsistent stimuli (P=0.048). Conclusion: Overweight adolescents have significant cognitive impairment, with significantly elevated serum FGF21 levels, and elevated FGF21 levels are independently associated with poorer overall cognitive and executive functions.